Cultural Communication and Inheritance of Slametan Ritual Food Values - Rahma Maulinda Dwinari; Muhammad Rio Fariza; Andre Noevi Rahmanto; Pawito Pawito (Jurnal ILMU KOMUNIKASI, 2026)
Globalization threatens the sustainability of Slametan tradition among youth. This study aims to uncover the communicative mechanisms of inheriting ritual food values in Gunungsari Village, Wonogiri Regency. This study gathered data from 15 cross-generational informants using a qualitative ethnography of communication framework and symbolic interactionism. Findings reveal that cultural inheritance occurs via domestic interaction, rewang, and formal rituals. Crucially, a symbolic reconciliation exists where digital media validates traditions for skeptical youth. The study concludes that Slametan tradition survives through a triangulated communication system: family, community, and digital validation, ensuring Javanese cultural resilience by harmonizing modern logic with traditional norms.